Kuwentong bayan :noong panahon ng Hapon everyday life in a time of war - Kintanar, Thelma B. (2006)
History of the social conditions during Japanese occupation in the Philippines.
Keywords: Philippines -- History -- Social conditions. -- Japanese occupation, 1942-1945.; Philippines -- History -- Japanese occupation, 1942-1945 -- Personal narratives